Estimating Capital Formation and Capital Stock by Economic Sector in China : The Implications for Productivity Growth - Herd, Richard (World Bank, Washington, DC, 2020)
This paper aims to fill a gap in the literature on capital formation in China by estimating the capital stock in four economic sectors: business, infrastructure, government, and housing. Such a breakdown is necessary for the purpose of analysis of economic development in China, as the normal models of economic development are based on a competitive economy, which is clearly not the case for the country's infrastructure and government sectors. Moreover, the contribution of housing to gross domestic product in China is very poorly measured. Although the results of this analysis can only be approximate, as the required detailed information for a better estimate is not published, they nonetheless suggest that there has not been overinvestment in the Chinese business sector -- its capital-output ratio has risen only slightly over the past 40 years. Yet, there have been surges in the stocks of housing and infrastructure in the past decade. These sectors account nearly all the recent increase in the capital-output ratio in China.